An integration of the dentistry with obstetricians and paediatric public health services in the implementation of the major oral diseases prevention program for children - Леус, Петр Андреевич (Actual Dentistry, 2019)
The Aim of this work was a proposed more closer integration of dentistry with other public health services on the strengthening effectiveness of dental caries prevention among young children. Methods. Meta-analysis of dental literature on the oral diseases descriptive and analytical epidemiology in connection with the running preventive measures among pregnant women and expecting mothers. The Minsk school oral health centre activities were analysed in the preventive program implementation. Results. An optimal model for integrating activities of dentists, obstetricians and paediatricians was proposed in the practical realisation of the preventive program, particularly among high school children, pregnant women and young mothers. Due to the integrated preventive program implementation, a prevalence of dental caries in permanent dentition among 7-year-old children has reduced to the level of 0.02–0.07 DMFT. Conclusion. The integration of dentists, obstetricians and paediatricians is important for an effective realisation of the long-term aims in oral diseases prevention among children. Key words: oral diseases prevention, integrating program, prenatal prevention, school oral health centre, monitoring dental health.